Thermodynamic analysis and comparison of mechanical subcooling transcritical CO2 refrigeration system with expander and throttling valve - Zeye Zheng; Qichao Yang; Wenting Zhang; Yuanyang Zhao; Guangbin Liu; Liansheng Li (Case Studies in Thermal Engineering)
Mechanical subcooling is an efficient means of enhancing the performance of CO2 transcritical refrigeration systems. With the aim of further improving the system performance, this objective of this paper is the comparative analysis on mechanical subcooling CO2 transcritical refrigeration system integrated with throttling valve (MCVS) and expander (MCES). A thermodynamic model for parametric analysis was developed on energy, exergy and economic perspectives. The model is validated with literature data. The simulation results indicate that there exists simultaneously optimum discharge pressure and subcooling degree maximizes the COP of MCVS and MCES. While the cooling capacity of MCES is 4.30 %–5.67 % lower than that of MCVS at a given CO2 mass flow rate, the incorporation of expansion work recovery leads to a total power consumption reduction of 8.53 %–11.29 % for MCES compared to MCVS, resulting in a corresponding increase in COP by 10.01 %–11.11 %. Additionally, exergy efficiency is improved by 10.74 %–11.48 %. Despite the addition of an expander in the MCES system, it offers advantages such as a smaller scale and lower power consumption for the mechanical subcooling system, ultimately leading to superior economic benefits compared with the MCVS system.